A snake that bites its own tail. Acquisition and loss of concepts in children and semantic dementia patients through the analysis of drawings. (July 2020) - Pozueta, Ana; Lage, Carmen; García-Martínez, María; Kazimierczak, Martha; Bravo, María; López-García, Sara; Fernández-Rodríguez, Andrea; Riancho, Javier; González-Suárez, Andrea; Vázquez-Higuera, José Luis; Cano-Abascal, Ángel; Martínez-Dubarbie, Francisco; et al.
Abstract: Objective: The structure of the semantic network is constructed and organized during childhood development. Previous publications have hypothesized that neurodegenerative diseases would lead to a disruption of this network reversing the steps acquired in childhood. Semantic Dementia (SD) is a subtype of frontotemporal lobe degeneration in which the main symptom is a specific loss of semantic memory. We aimed to describe the sequential acquisition of concepts in 3-8 years old children evaluated through the production of drawings and, in parallel, their progressive loss in SD patients. Methods: 104 children between 40 and 96 months categorized into tertiles according to their age, 21 SD patients categorized into tertiles according to their score on a category fluency task and 34 healthy volunteers were asked to draw 12 items with, a priori, different age of acquisition and familiarity, belonging to four different semantic categories. We employed the drawings of the healthy volunteers to build a scoring scheme. We considered that a concept was acquired in children when 50% or more of its features were present in their drawings, and it was lost in patients when more than 50% were missing. Results: Those concepts which the children were able to acquire earlier, according to our scoring scheme, tended to remain in patients with more advanced SD. While the items that children acquired later, were, in general, those that the SD patients lost at earlier disease stages. Conclusion: The patterns of concept acquisition in children were the mirror image of the loss in patients with SD. Our study supports the hypothesis that the sequence of concept acquisition in childhood is reversed in SD patients.